2022
DOI: 10.3389/fmolb.2022.1102158
|View full text |Cite
|
Sign up to set email alerts
|

Targeting GSTP1-dependent ferroptosis in lung cancer radiotherapy: Existing evidence and future directions

Abstract: Radiotherapy is applied in about 70% patients with tumors, yet radioresistance of tumor cells remains a challenge that limits the efficacy of radiotherapy. Ferroptosis, an iron-dependent lipid peroxidation regulated cell death, is involved in the development of a variety of tumors. Interestingly, there is evidence that ferroptosis inducers in tumor treatment can significantly improve radiotherapy sensitivity. In addition, related studies show that Glutathione S-transferase P1 (GSTP1) is closely related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Finally, catalysed by lipoxygenase (LOX), PUFAs‐PE can be oxidised, contributing to lipid peroxidation and thereby inducing ferroptosis. 46 Therefore, the expressions of ACSL4 in those ferroptosis‐sensitive cells such as HepG2 and HL60 are higher than that in such ferroptosis‐resistant cells as LNCaP as well as K562. 47 In addition, compared with control MLE cells, LPCAT3 knockdown MLE cells are resistant to RSL3‐induced ferroptosis, showing lower rate of cell death.…”
Section: Overview Of Ferroptosismentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, catalysed by lipoxygenase (LOX), PUFAs‐PE can be oxidised, contributing to lipid peroxidation and thereby inducing ferroptosis. 46 Therefore, the expressions of ACSL4 in those ferroptosis‐sensitive cells such as HepG2 and HL60 are higher than that in such ferroptosis‐resistant cells as LNCaP as well as K562. 47 In addition, compared with control MLE cells, LPCAT3 knockdown MLE cells are resistant to RSL3‐induced ferroptosis, showing lower rate of cell death.…”
Section: Overview Of Ferroptosismentioning
confidence: 94%
“…Subsequently, LPCAT3 combines PUFAs‐CoA with PE, thus producing PUFAs‐PE. Finally, catalysed by lipoxygenase (LOX), PUFAs‐PE can be oxidised, contributing to lipid peroxidation and thereby inducing ferroptosis 46 . Therefore, the expressions of ACSL4 in those ferroptosis‐sensitive cells such as HepG2 and HL60 are higher than that in such ferroptosis‐resistant cells as LNCaP as well as K562 47 .…”
Section: Overview Of Ferroptosismentioning
confidence: 99%
“…However, there is insufficient evidence to determine whether immunotherapy for lung cancer could also be linked to ferroptosis. 113 , 116 Despite extensive research in recent years, the relationship between tumor immunity and ferroptosis, including its effects on tumor susceptibility, is not well understood.…”
Section: Ferroptosis In Respiratory Diseasesmentioning
confidence: 99%
“…Another study in prostate cancer showed that piR-31470 forms a complex with piwi-like RNAmediated gene silencing 4 (PIWIL4) and then recruits DNMT1, DNA methyltransferase 3α, and methyl-CpG binding domain protein 2 to initiate and maintain the hypermethylation and inactivation of glutathione S-transferase P1 (GSTP1) [175]. Related studies have indicated that GSTP1 inactivation inhibits tumor cells from evading ferroptosis, leading to tumor growth [176], suggesting that piR-31470 may suppress ferroptosis through the inactivation of GSTP1.…”
Section: Pirnas In Ferroptosismentioning
confidence: 99%